Does Proximity Matter in the Choice of Partners in Collaborative R&D Projects? – An Empirical Analysis of Granted Projects in Germany - Clemens Fuhrmeister; Mirko Titze; Ulrich Blum; Philipp Marek (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2014)
This paper contributes to the discussion on the importance of physical distance in the emergence of cross-region collaborative Research and Development (R&D) interactions. The proximity theory, and its extensions, is used as a theoretical framework. A spatial interaction model for count data was implemented for the empirical analysis of German data from the period from 2005 to 2010. The results show that all tested proximity measurements (geographical, cognitive, social and institutional proximity) have a significant positive influence on collaboration intensity. The proximity paradox, however, cannot be confirmed for geographical, social and institutional proximity, but for cognitive proximity. – – Das Papier leistet einen Beitrag zur Diskussion über die Bedeutung physischer Distanz für die Herausbildung von Zusammenarbeit in der Forschung und Entwicklung (FuE) über Regionsgrenzen hinweg. Den theoretischen Rahmen bilden die Proximity-Theorie und ihre Erweiterungen. Mit Hilfe eines räumlichen Interaktionsmodells für Zähldaten werden deutsche Daten des Zeitraums von 2005 bis 2010 empirisch analysiert. Die Ergebnisse zeigen, dass alle getesteten Maße für Nähe (geographische, kognitive, soziale und institutionelle) einen signifikant positiven Einfluss auf die Intensität der Zusammenarbeit haben. Das 'Paradox der Nähe' kann hingegen nur für kognitive Nähe bestätigt werden, nicht aber für geographische, soziale und institutionelle Nähe.
urn:nbn:de:gbv:3:2-36169
Keywords: O18; R00; R11; 330; proximity theory; proximity paradox; gravity models; cross-regional collaborations; spatial interaction; Proximity-Theorie; Nähe-Paradox; Gravitationsmodell; regionenüberschreitende Zusammenarbeit; räumliche Interaktion